(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
This paper proposes to transform microwaves for snow melting, which slightly leaking from the slotted waveguide, into electric power using a wireless power transmission technique for effective use. A combination of left-handed and right-handed waveguides is a method to melt snow evenly over a large area using microwaves. The left-handed waveguide, however, has large loss because of stubs. In order to evaluate the effect of the left-handed waveguide’s loss, this paper analyzed the wireless power transmission efficiency when the left-handed waveguide with a slot was set as the power transmission part, and a dipole array was placed above the left-handed waveguide as a power reception unit. The wireless power transfer efficiency was calculated using kQ product from S-parameters that were obtained by using the method of moments. The results clarified that the sum of the maximum efficiencies of the arrayed dipoles could be made larger than the maximum efficiency of one dipole.